ANALISIS DINAMIK STRUKTUR MENARA USM DENGAN METODE RESPONS SPEKTUM - Trias Widorini; Ngudi Hari Crista; Kukuh Wisnuaji Widiatmoko (Politeknik Negeri Semarang, 2022)
The USM tower consists of 10 floors used as offices, parking and educational facilities with a total height of 48.5 m. Earthquake resistance analysis needs to be carried out on buildings built in earthquake areas. This study uses dynamic analysis with the response spectrum method, aiming to evaluate the structure according to SNI 1726:2012. What is reviewed in this study is the period, base shear, drift, and the level of building performance. The results of the analysis show that the period, base shear, drift and the maximum deviation meet the specified requirements. The USM Tower's performance level is Immediate Occupancy according to ATC-40 regulations.